2014
DOI: 10.1097/ccm.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Spiritual Care Providers’ Activities With Family Members’ Satisfaction With Care After a Death in the ICU*

Abstract: Objective Spiritual distress is common in the ICU, and spiritual care providers are often called upon to provide care for patients and their families. Our goal was to evaluate the activities spiritual care providers’ conduct to support patients and families, and whether those activities are associated with family satisfaction with ICU care. Design Prospective cohort study. Setting 350-bed, 65-ICU bed tertiary care teaching hospital. Subjects Spiritual care providers and family members of patients who die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
97
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 34 publications
(37 reference statements)
2
97
1
3
Order By: Relevance
“…9,10,53,54,[59][60][61][62][63][64][65][66][67][68][69][70][71]76,77 These studies are reported between 2002 and 2014.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10,53,54,[59][60][61][62][63][64][65][66][67][68][69][70][71]76,77 These studies are reported between 2002 and 2014.…”
Section: Settingmentioning
confidence: 99%
“…Most of the studies were based in North America -the USA (n = 9) 53,54,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][76][77][78][79][80] and Canada (n = 3) 9,10,56,74 -with other studies based in Greece (n = 2), 41,42 Switzerland (n = 2), 17,55 Germany (n = 1), 39 Israel (n = 1), 57 the Netherlands (n = 1), 75 the Philippines (n = 1) 38 and Turkey (n = 1). 40 Nine studies were single centre, with the remainder being multicentre, ranging from 2 to 23 centres.…”
Section: Settingmentioning
confidence: 99%
“…We specifically measured participants' emotions, showed improvement in symptoms of anxiety and stress, and elicited feedback that suggests spiritual care helps ICU survivors cope with critical illness. Prior studies have shown that chaplain-led spiritual care improves family satisfaction with end-of-life care in the ICU (23,24), but our study is the first to proactively and systematically engage mechanically ventilated ICU patients who are not necessarily dying. With technological advances, many critically ill patients now survive what were previously fatal illnesses (40,41), but survivors of mechanical ventilation are increasingly recognized to suffer from anxiety, depression, and posttraumatic stress disorder (42)(43)(44).…”
Section: Original Researchmentioning
confidence: 99%
“…took the chaplain a median (IQR) of 18 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) minutes to both use the card with participants and provide a desired spiritual care intervention (Table 2). For 34 participants (68%), identifying a spiritual affiliation consisted of the chaplain pointing to the affiliation on the card that was listed in the medical record or given by family members and observing the subject nod in acknowledgment.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation